Theorising the relationship between kalām and uṣūl al-fiqh: the theological-legal epistemology of Saʿd al-Dīn al-Taftāzānī (d. 792/1390) - Ahmad, NN (2018)
This thesis examines the appropriation and naturalisation of philosophical theology (kalām) and Arabic logic (manṭiq) into Islamic legal hermeneutics (uṣūl al-fiqh) in the 8th/14th century in the works of the Persian theologian cum jurist Saʿd al-Dīn al-Taftāzānī (d. 792/1390). By the 5th/11th centaury, uṣūl al-fiqh works across madhhabs contained an extensive introduction on epistemology. This practice brought two main questions: the first is concerning the classification of the sciences and their hierarchy (whether this epistemological introduction pertains to an Islamic science, kalām, or a non-Islamic science, logic). The second is concerning the status and function of uṣūl al-fiqh as a key contributor to the late-classical rational sciences. This thesis offers an original contribution to answering these two questions. It studies the development of uṣūl al-fiqh as a source of epistemology through investigating its relationship to kalām and Arabic logic. More specifically, it investigates the so-called theological principles (al-mabādi’ al-kalāmiyya) as they appear in the above three sciences from the 11th to the 14th centuries. The analysis in this thesis shows that these mabādi’ play an epistemological role, insofar as they deal with the objects and classification of knowledge (ʿilm and ẓann), the character and typology of epistemic indication (dalāla), and the nature of theoretical investigation (naẓar). The main features of these theories, this study shows, are their occasionalist and foundationalist concerns, developed through three centuries of debates. This thesis also offers new insights on the features of Taftāzānī’s intellectual project, concluding that the originality of Taftāzānī’s thought is best seen in his concern with scholastic verification (taḥqīq), spurning madhhab-affiliations.